LEGAL PROTECTION FOR VICTIMS OF CRIMINAL VIOLATIONS (CASE STUDY OF VIOLENCE AGAINST CHILDREN IN BULELENG DISTRICT) - Yuliartini, Ni Putu Rai (Veteran Law Review, 2019)
This research aims to analyze the form of legal protection against child victims of violence in Buleleng. In addition, this research also analyzes the obstacles and efforts made by Buleleng police in uncovering cases of child abuse in Buleleng. This research is an empirical study with a study that sees law as a reality that includes social reality, reality of culture and others (examine law in action). This empirical law study aims to examine legal issues in its practical dimensions, especially related to legal protection for victims of violent crime in Buleleng district. This research uses primary data and secondary data with research location in Buleleng. Technique of collecting data is done through observation and interview. The collected data is then processed and analyzed qualitatively. The results of this study indicate that the Buleleng police prepare by receiving reports or complaints from victims of violence, whether orally or in writing as a form of regulation. The place for report or complain is on the section integrated police service center. Basically legal protection against child victims of violence is conducted in accordance with the Child Protection Act. Basically legal protection against child victims of violence is conducted in accordance with the Child Protection Act. While related to obstacles faced by Buleleng police in revealing cases of violence that occur to children that investigators often have difficulty in finding the perpetrators, lack of information from perpetrators or victims, chronology is often covered, not conformity information between perpetrators and victims. In addition, investigators find it difficult to obtain information or information from traumatized victims, lacking evidence, obstacles to finding witnesses, and the results of their visum. Furthermore, related to the efforts made, Buleleng police conducted the process of receiving reports or complaints from families of victims who experienced violence. In addition, assistance was also provided by the integrated service center for the empowerment of women and children in Buleleng, in the case of violence that occurred was accompanied, mainly related to cases of sexual violence. The involvement of an integrated service center for the empowerment of women and children is to further strengthen the mental victim through psychological support. Not only get assistance from integrated service centers for women and children empowerment but also receive assistance from social services.